Two new species of Gymnopus sect. Levipedes (Omphalotaceae, Agaricales) from Central and North China - Jia-Jun Hu; Yong-Lan Tuo; Zheng-Xiang Qi; Dong-Hua Jiang; Yu Li; Bo Zhang (MycoKeys)
The genus Gymnopus has a long research history and is known for its high species diversity worldwide. However, its species diversity in China remains poorly understood. Through a combination of detailed morphological studies and phylogenetic analysis, this study described two new species from Northeast and Central China, Gymnopus biyangensis and Gymnopus sinodryophilus, both belonging to Gymnopus sect. Levipedes. Gymnopus biyangensis is characterized by basidiomata appearing in summer and originating from broad-leaved forests, a dark reddish-brown pileus, a cylindrical to clavate stipe, and clavate to cylindrical, diverticulate cheilocystidia. Gymnopus sinodryophilus differs by the yellowish-white to light brown basidiomata arising from coniferous and broad-leaved mixed forests, coralloid but inflated pileipellis terminal cells, and an apex of cheilocystidia not coralloid. Additionally, a key to the reported species of Gymnopus sect. Levipedes in China is provided.